Differentiated Learning Strategies in Indonesian Language Subjects for Grade IV - Muhamad Yusuf; Hidayat Hidayat (Papanda Publisher, 2026)
Differentiated inquiry-based learning represents a promising approach for addressing diverse student needs in elementary literacy instruction, yet empirical evidence regarding its implementation in Indonesian language contexts remains limited. This qualitative case study examined differentiated learning strategies in fourth-grade Indonesian language instruction at two elementary schools in West Jakarta. Data were collected through classroom observations, semi-structured interviews with principals, teachers, and students, and document analysis of teaching modules and assessments. Analysis followed Miles, Huberman, and Saldaña's framework, with triangulation ensuring trustworthiness. Pretest-posttest comparisons revealed substantial literacy gains, with reading scores improving 17.4 points and writing scores 17.6-20.7 points across schools. Student surveys indicated significant increases in motivation (68%), self-confidence (75%), and engagement (80%). Teachers successfully implemented content, process, and product differentiation while integrating inquiry-based activities. However, implementation faced challenges including time constraints (100% of teachers), resource limitations (88%), and pedagogical complexity (75%). Unexpectedly, peer learning dynamics emerged organically, with students spontaneously adopting teaching roles. Findings support Tomlinson's differentiation framework and Vygotsky's constructivism, demonstrating that inquiry-based differentiation enhances both cognitive and affective outcomes. However, successful implementation requires systemic support including dedicated planning time, graded resources, and sustained professional development. This study contributes theoretical understanding of integrating differentiation with inquiry using systematic planning models while offering practical implications for Merdeka Curriculum implementation.